Electronic structure and properties of Cd4As2Br3 and Cd4Sb2I3, analogues of CdSe and CdTe. (April 2017) - Roy, Anand; Suchitra,; Manjunath, K.; Ahmad, Tokeer; Waghmare, Umesh V.; Rao, C.N.R.
Abstract: Substitution of aliovalent anions in metal oxides and chalcogenides significantly affects the electronic structure and properties of the materials. Thus, substitution of P 3- and Cl - in CdS decreases the band gap and favorably influences the photocatalytic activity. Complete substitution of a trivalent (A 3- ) and a monovalent (B - ) anions in a cadmium chalcogenides, CdX, should give rise to a material of the composition Cd A0.5 B0.5 or Cd2 AB, but a compound with the composition Cd4 P2 Cl3 (or Cd2 PCl1.5 ) is obtained in the case of CdS. We have investigated the analogous compounds, Cd4 As2 Br3 and Cd4 Sb2 I3, wherein the anions in CdSe and CdTe are substituted by As, Br and Sb, I respectively. These compounds are direct band gap semiconductors with a band gap of 1.8–1.9 eV and a photoluminescence band in the visible region. First-principles calculations show both Cd4 As2 Br3 and Cd4 Sb2 I3 to be direct band gap semiconductors. The arsenic bromide is predicted to be photochemically more active for HER than the antimony iodide. Graphical abstract: Highlights: A detailed study of the electronic structure and photo-physical properties of Cd4As2Br3 and Cd4Sb2I3 has been carried. Cd4AS2Br3 and Cd4Sb2I3 show direct band gaps of 1.93 and 1.80 eV and photoluminescence in the visible region. Time resolved photoluminescence decay suggests average life time of charge carrier to be of 2 ns. First principles calculations predict that these semiconductors can be utilized for HER from water splitting. HER activity of these compounds has also been investigated experimentally.